Pengendalian Gula Darah pada DM Tipe 2 dengan Pemeriksaan HbA1c di Rumah Sakit - Wuni Sri Lestari; Eka Fitriana; Akhirul Jumaisa; Sarinah Siregar; Sri Ujiani (Journal of Telenursing (JOTING), 2022)
This study aims to determine the control of blood sugar levels in type 2 DM patients at Raden Mattaher Hospital Jambi. The design of this study was descriptive analysis using 100 samples of type 2 DM patients who underwent inpatient and outpatient treatment while blood sugar and HbA1c were checked. The results showed 82 patients with uncontrolled HbA1c levels with an average HbA1c level of 10.11% and 78 patients with abnormal blood sugar levels with an average blood sugar level of 326 mg/dL. Most patients with type 2 diabetes are female (61%), early adulthood 18-40 years (61%), obesity BMI (50%), moderate activity (52%) and poor diet (59%). Based on the characteristics of the respondents, it was found that HbA1c levels were not controlled in the groups: middle adults (85.2%), women (80.3%), BMI with obesity (86.0%), light activity (81.8%) and poor diet. (86.4%). In conclusion, most of the samples were included in the criteria for poor DM control based on current blood sugar levels and HbA1c. Keywords: Type 2 DM, Temporary Blood Sugar, HAa1c, Blood Sugar Control